Mapping Sexual Abuses towards Children in India - Bharali, Tridib (International Journal of Psychosocial Rehabilitation, 2020)
There are 444 million children in India under the age of 18 years. This constitutes 37% of the total population in the country. Children have all the rights as equal to citizens of India, just as any other adult male or female. But the irony is that there is a huge upsurge of violations of children rights in our society in different forms including rapes in its brutal form, some are traced and some untraced. In order to deal with the problem, the mechanism that is right now in force is the Protection of Children from Sexual Offences Act (POCSO), 2012. The statistics and the observations made by the author through this paper is an attempt to highlight the most contemporary discourse of the hour on the issue that is the sexual abuses towards the children. It argues that though there are a number of civil society organizations and framed legislations, the menace of such abuses is not being truly contained which in turn raises serious questions on the existing state legislations, machineries and society’s role in this regard.